Formações de professores e a arte de um fazer(se) em intervalos: imagens em movimento - Solis, Vanessa Oliveira (2010)
The aim of this study is to comprehend the dimensions of the word/narrative and look/image while experiences which contribute to the meaning itself and the professor on a formation process. For this, there were realized five meetings with the purpose of a free writing to discuss pre selected and projected movies. Along it, the research group could experience going through image/word and meetings on these three forms of stimulation: the image, the word and the writing. This study is characterized by a qualitative research, as a study of case, where the data assessment was the individual observation and the filming of the discussions. Data analysis was obtained with the narrative method in which the Conversation is taken as an instrument of research with groups through psychoanalysis and education. The study is important because it gives a space to the people on this research, young students of the Universidade Federal de Santa Maria, then they can understand their own formative process.